(untitled) - Datta, Supriyo (Cambridge, 2005)
Including some of the most advanced concepts of non-equilibrium quantum statistical mechanics, this book presents the conceptual framework underlying the atomistic theory of matter. No prior acquaintance with quantum mechanics is assumed. Many numerical examples provide concrete illustrations, and the corresponding MATLAB codes can be downloaded from the web. Videostreamed lectures linked to specific sections of the book are also available through web access.
Keywords: Điện tử lượng tử,Quantum electronics